Orientation and conformation of two [6]carbohelicenes in stretched polystyrene and a thermoresponsive polyaspartate. (6th August 2019) - Doppler, Anna; Nicholls, Leo D.M.; Golz, Christopher; Alcarazo, Manuel; John, Michael
Abstract: Two functionalized [6]carbohelicenes, one of which was also available in its two enantiomeric pure forms, were oriented in stretched polystyrene in CDCl3, and in a recently introduced chiral thermoresponsive lyotropic polyaspartate (poly(benzyl)0.5 (phenethyl)0.5 ‐L‐aspartate) in C2 D2 Cl4 . From the resulting 1 H, 13 C residual dipolar couplings, the helical pitch of a methylated [6]carbohelicene was determined and found to be in agreement with theoretical predictions and existing crystal structures ( d (C2, C2′) ≈ 4.3 Å). For a second [6]carbohelicene with para ‐methoxyphenyl substituents, a clear conformational preference of the substituents was observed. The orientational properties of the two helicene enantiomers in the chiral polyaspartate are very similar, but both drastically change around 306 K. We suggest this behavior is due to an unusual phase transition in the liquid crystal. Abstract : Residual dipolar couplings (RDCs) in two alignment media were used to determine helical pitch and substituent conformation in two [6]carbohelicenes. Temperature‐dependent orientation and diffusion in the thermoresponsive polyaspartate suggest an unusual phase transition.